Exploring the attitudes towards and experiences of geocaching amongst families in the community - Robinson, S.; Hardcastle, Sarah (Taylor & Francis, 2016)
There is a need for physical activity interventions to focus on autonomous forms of motivation to increase uptake and maintenance. Geocaching is a GPS-based treasure-hunt game with potential to increase levels of walking. The study aim was to explore the experiences of a geocaching intervention for people introduced to geocaching. A five-week geocaching intervention took place. Participants (n = 30) were recruited via school assemblies and village posters. Semi-structured telephone interviews (n = 21) were conducted post intervention to determine the participants' motives, barriers and experiences of geocaching. Geocaching motivators (social activity, challenge/discovery) and barriers (lack of time, problems with mobile technology and unsuccessful trips) were identified. Findings suggest that geocaching is a feasible activity to promote physical activity, particularly among families. Further robust and larger scale trials are required that target sedentary individuals, adopting strategies to reduce perceived barriers to geocaching.